Effects of training on resting plasma levels of homocysteine and C-reactive protein in competitive male and female wrestlers - Hübner-Wozniak, E.; Ochocki, P. (Biomedical Human Kinetics, 2009)
Study aim: To assess the effects of training on resting plasma levels of homocysteine (Hcy), C-reactive protein (CRP), folic acid, and on the activity of creatine kinase (CK) in competitive male and female wrestlers. Material and methods: Polish elite wrestlers, male MW; n = 11) and female (FW; n = 11), as well as corresponding numbers of untrained, control subjects (MC and FC, respectively), participated in the study. Blood for assays was withdrawn from the antecubital vein in the morning, in pre-prandial state. Homocysteine (Hcy), C-reactive protein (CRP), folic acid and creatine kinase (CK) activity were assayed in plasma. Results: Mean concentrations of Hcy and CRP were in the control groups significantly higher and those of folic acid - lower than in the respective groups of wrestlers. Folic acid levels were negatively correlated with Hcy, especially in wrestlers (r = -0.540; p<0.01). Mean CK activity was significantly (p<0.001) higher in male wrestlers than in male controls or female subjects. No significant correlation between CK and CRP was found. Conclusions: Strength-speed training practiced by elite wrestlers, associated with significantly lower values of Hcy and CRP in them compared with the untrained subjects, may reduce the risk of cardiovascular diseases at later age, like in case of endurance training.